Community representation and policing: Effects on Black civilians - Risi, Joseph (Criminology, 2024)
Does increased representation of Black individuals in the police force lead to less aggressive policing of Black individuals? The current study uses a Chicago panel data set with monthly police unit observations between 2013 and 2015 to understand 1) how police units’ representation of Black individuals affects the number of stops of Black residents and 2) how individual police officers patrol differently depending on the racial/ethnic background of co-working officers. Using fixed-effects negative binomial regression, we found that increasing racial congruence between police officers and the community being patrolled was associated over time with fewer stops of Black residents. Individual analyses showed that Black (vs. White) officers stopped fewer Black civilians, with larger effects in police units with higher percentages of Black officers, indicating a unit group effect. Furthermore, as the number of Black officer co-workers in a shift increased, Black civilian stops declined for all officers, including White officers, which is consistent with active representation. These findings indicate that a more diverse and representative police force can reduce aggressive policing of minority communities by mitigating group threat and cultivating positive cross-racial exchanges within police organizations and smaller peer groups.